2012
DOI: 10.1111/are.12103
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of European sea bass,Dicentrarchus labraxL., in cages - impact of early life rearing conditions and management

Abstract: European sea bass, Dicentrarchus labrax L., groups reared under different conditions during larval stages (mesocosm and intensive rearing) were monitored during on-growing in sea cages until marketable size (350-400 g). Four caged groups were followed for a period of 17 months each at a pilot scale farm, where vertical distribution behaviour was monitored. This was performed while fish were under calm conditions, during feeding and when stress events occurred. Also during two specific periods: (i) spawning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The sound exposure might have caused both diving to deeper depths and an increased heart rate. Other studies have shown that fish may move to deeper depths during stress (Papandroulakis et al , 2014; Neo et al , 2018). No significant diving behaviour after sound exposures was observed in the video data.…”
Section: Discussionmentioning
confidence: 96%
“…The sound exposure might have caused both diving to deeper depths and an increased heart rate. Other studies have shown that fish may move to deeper depths during stress (Papandroulakis et al , 2014; Neo et al , 2018). No significant diving behaviour after sound exposures was observed in the video data.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, rapid capture by luring fish to the surface via feed pellets resulted in low basal cortisol concentrations. It should, however, be kept in mind that when feed is supplied, E. sea bass fish perform a ‘tornado‐like’ movement, which describes the creation of a vortex by the fast movement of the fish in a circle (Papandroulakis, Lika, Kristiansen, Oppedal, Divanach & Pavlidis ). It could, therefore, be possible that more competitive fish may overtake less competitive ones in the feeding area, as these high densities in the upper layer of the water surface suggest high competition between con‐specifics (Andrew, Noble, Kadri, Jewell & Huntingford ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, group swimming behaviour appears to be a sensitive welfare indicator even if it is still lacking calibration efforts to be precisely translated into an operational welfare indicator; nevertheless some examples exist (Papandroulakis et al, 2014;Pettersen et al, 2014). Moreover, the appraisal of negative or positive stimuli and, hence, the psychological dimension of stress as defined for fish by Galhardo and Oliveira (2009) is seldom tackled in welfare research.…”
Section: J O Umentioning
confidence: 99%